1988
DOI: 10.1042/bj2540789
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of phenobarbital-inducible cytochrome P-450s in rat and mouse liver following dexamethasone administration and hypophysectomy

Abstract: Cytochrome P-450s are a superfamily of haem-containing proteins involved in the metabolism of foreign compounds, as well as a variety of endogenous molecules. The hepatic levels and function of this diverse group of enzymes are determined by both constitutive and xenobiotic regulators. To examine the role of constitutive factors in cytochrome P-450 regulation, the levels of three distinct groups of phenobarbital-inducible hepatic cytochrome P-450s were studied following dexamethasone-treatment or hypophysectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 35 publications
2
49
1
Order By: Relevance
“…Treatment of WT and huPXR mice with the potent mouse inducer dexamethasone (DEX) (14,30) resulted in a much more marked consistent induction in WT than in huPXR mice. At doses of up to 10 mg/kg, induction of Cyp3a11 was only observed in WT but not huPXR mice ( Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of WT and huPXR mice with the potent mouse inducer dexamethasone (DEX) (14,30) resulted in a much more marked consistent induction in WT than in huPXR mice. At doses of up to 10 mg/kg, induction of Cyp3a11 was only observed in WT but not huPXR mice ( Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…The marked species differences in the induction of phase I, II, and III enzymes in response to various compounds raise a difficulty in extrapolating metabolism data across species (30,(38)(39)(40)(41). Taking into account the relevance of drug metabolizing enzyme and transporter induction or repression for drug safety and efficacy, these species differences clearly limit the significance of animal tests in respect to the situation in humans.…”
Section: Discussionmentioning
confidence: 99%
“…[dexamethasone (Waxman et al, 1985;Wrighton et al, 1985;and Meehan et al, 1988)] forms on the metabolism of VCH and testosterone. In hepatic microsomes isolated from phenobarbital pretreated mice VCH epoxidation was increased 5.7-fold ( Figure 9).…”
Section: Immunochemical Methodsmentioning
confidence: 99%
“…In addition, submicromolar concentrations of DEX also enhance the expression of the constitutive androstane receptor (CAR) and the retinoid X receptor-␣ in human hepatocytes (Pascussi et al, 2000a,b). It has been shown that DEX is a more potent ligand for mouse PXR than the human receptor (Meehan et al, 1988;Moore et al, 2000), and hepatic induction of Cyp3a, but not Cyp2b, expression in mice is PXRdependent (Schuetz et al, 2000;Scheer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, submicromolar concentrations of DEX also enhance the expression of the constitutive androstane receptor (CAR) and the retinoid X receptor-␣ in human hepatocytes (Pascussi et al, 2000a,b). It has been shown that DEX is a more potent ligand for mouse PXR than the human receptor (Meehan et al, 1988;Moore et al, 2000), and hepatic induction of Cyp3a, but not Cyp2b, expression in mice is PXRdependent (Schuetz et al, 2000;Scheer et al, 2008).CYP3A plays a central role in DEX disposition in human liver because it catalyzes the formation of the two major metabolites, 6␣-and 6␀-hydroxy-dexamethasone (Gentile et al, 1996). Indeed, the relatively simple metabolic profile of DEX compared with many other substrates led to the proposal that DEX would be a useful in vivo probe for CYP3A4 activity (Gentile et al, 1996).…”
mentioning
confidence: 99%